The spatial and temporal distribution of grain‐size breaks in turbidites. Issue 4 (21st March 2014) - Stevenson, Christopher J.; Talling, Peter J.; Masson, Douglas G.; Sumner, Esther J.; Frenz, Michael; Wynn, Russell B.; Baas, Jaco
ABSTRACT Grain‐size breaks are surfaces where abrupt changes in grain size occur vertically within deposits. Grain‐size breaks are common features in turbidites around the world, including ancient and modern systems. Despite their widespread occurrence, grain‐size breaks have been regarded as exceptional, and not included within idealized models of turbidity current deposition. This study uses ca 100 shallow sediment cores, from the Moroccan Turbidite System, to map out five turbidite beds for distances in excess of 2000 km. The vertical and spatial distributions of grain‐size breaks within these beds are examined. Five different types of grain‐size break are found: Type I – in proximal areas between coarse sand and finer grained structureless sand; Type II – in proximal areas between inversely graded sand overlain by finer sand; Type III – in proximal areas between sand overlain by ripple cross‐laminated finer sand; Type IV – throughout the system between clean sand and mud; and Type V – in distal areas between mud‐rich (debrite) sand and mud. This article interprets Types I and V as being generated by sharp vertical concentration boundaries, controlled by sediment and clay concentrations within the flows, whilst Types II and III are interpreted as products of spatial/temporal fluctuations in flow capacity. Type IV are interpreted as the product of fluid mud layers, which hinder the settling of non‐cohesive grains and bypasses them down slope. Decelerating suspensions with sufficient clay will always form cohesive layers near to bed, promoting the generation of Type IV grain‐size breaks. This may explain why Type IV grain‐size breaks are widespread in all five turbidites examined and are commonplace within turbidite sequences studied elsewhere. Therefore, Type IV grain‐size breaks should be understood as the norm, not the exception, and regarded as a typical feature within turbidite beds.